2017
DOI: 10.1186/s12870-017-1159-3
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis from seeds in a broad range of Vitis vinifera L. varieties: rescue of true-to-type virus-free plants

Abstract: BackgroundSomatic embryogenesis is the preferred method for cell to plant regeneration in Vitis vinifera L. However, low frequencies of plant embryo conversion are commonly found. In a previous work we obtained from cut-seeds of a grapevine infected with the Grapevine leafroll associated viruses 1 and 3 (GLRaV-1 and GLRaV-3), high rates of direct regeneration, embryo plant conversion and sanitation. The aim of this study is to evaluate the usefulness of this procedure for regeneration of other grapevine variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Young K. paniculata seeds (Figure 1a) used as initial material have great potential for the induction of embryogenic calluses. Similar studies of other species have indicated that seeds are a good choice for embryogenic callus induction [29,34,49,50]. In addition, the genotype also has an effect on embryogenic callus induction rates.…”
Section: Other Factors Influencing Somatic Embryogenesismentioning
confidence: 62%
See 1 more Smart Citation
“…Young K. paniculata seeds (Figure 1a) used as initial material have great potential for the induction of embryogenic calluses. Similar studies of other species have indicated that seeds are a good choice for embryogenic callus induction [29,34,49,50]. In addition, the genotype also has an effect on embryogenic callus induction rates.…”
Section: Other Factors Influencing Somatic Embryogenesismentioning
confidence: 62%
“…Histological analyses of embryogenic calluses and somatic embryos were performed according to [21]. Plant materials were fixed in a fixative solution (formaldehyde:glacial acetic acid:alcohol, 8:1:1), and then dehydrated using graded ethanol (50,70,85,95, and 100% v/v). Processed materials were embedded in paraffin wax and cut using a microtome device (model no.…”
Section: Histologymentioning
confidence: 99%
“…The result obtained for GFkV was expected because this virus is not seed transmitted [75]. With respect to GLRaV-3, it is not clear if it is present in seeds [34,75], but we have found this virus in some regenerated plants resulting from somatic embryos induced from seeds of other infected grapevines, which would indicate its presence in the seeds [54]. Induction of somatic embryos from stamens or pistils was also reported in grapevine to cure plants of GLRaV [76,77].…”
Section: Virus Analysis and Sanitationmentioning
confidence: 59%
“…As occurred in other areas, grapevine cultivars were found commonly infected by the viruses GFLV, GLRaV, and GFkV. Sanitation of cultivars to be preserved in vitro is being carried out through meristem culture, although other alternative sanitation procedures are being developed [42,54]. In this work, we report the SSR profiles of different accessions of the historic variety "Valencí Blanc" or "Beba" and the historic and endangered variety "Esclafagerres" (or "Esclafacherres/is").…”
Section: Richness Of Grapevine Germplasm In the Comunitat Valencianamentioning
confidence: 99%
“…As occurred in other areas, grapevine cultivars were found commonly infected by the viruses GFLV, GLRaV and GFkV. Sanitation of cultivars to be preserved in vitro is being carried out through meristem culture, although other alternative sanitation procedures are being developed [42,54]. In this work, we report the SSR profiles of different accessions of the historic variety 'Valencí Blanc' or 'Beba and the historic and endangered variety 'Esclafagerres' (or 'Esclafacherres/is').…”
Section: Richness Of Grapevine Germplasm In the Comunitat Valencianamentioning
confidence: 99%